Deconversion and Disaffiliation in Contemporary US Roman Catholicism - Beaudoin, Tom (Horizons, 2013)
Disaffiliation—when members of religious communities leave—has recently become a popular topic for theological and social scientific investigation. Today, fewer Roman Catholics than in recent memory describe themselves as strong members of their church. Many have left to seek other spiritual paths, and many of those who remain do not believe and practice as the Church teaches that they should. These essays propose that the theoretical framework of "deconversion" provides a broader and more effective way to understand forms of religious change that are occurring in contemporary America. In the classroom, teaching theology can take on a specific productive shape when the surrounding culture challenges theologians to take deconversion seriously as an element of, and larger context for, spiritual identity today. Theology remains vital when patient curiosity about the current adventure of religious identity is foregrounded pedagogically. Concluding thoughts sketch some important characteristics of an evangelical church, more concerned with its mission and witness in the world than with maintaining its internal life.